Geoantineutrino spectrum, 3He/4He-ratio distribution in the Earth’s interior and slow nuclear burning on the boundary of the liquid and solid phases of the Earth's core - V. D. Rusov; V. N. Pavlovich; V.N. Vaschenko; V. A. Tarasov; T.N. Zelentsova; V. N. Bolshakov; D. A. Litvinov; S. I. Kosenko; O. A. Byegunova (Ukrainian Antarctic Journal, 2006)
The description problem of geoantineutrino spectrum and reactor antineutrino experimental spectrum in KamLAND, which takes place for antineutrino energy ~ 2.8 MeV, and also the experimental results of the interaction of uranium dioxide and carbide with iron-nickel and silica-alumina melts at high pressure (5-10 GPа) and temperature (1600-22000 C) have motivated us to consider the possible consequences of the assumption made by V.Anisichkin and coauthors that there is an actinid shell on boundary of liquid and solid phases of the Earth's core. We have shown that the activation of a natural nuclear reactor operating as the solitary waves of nuclear burning in 238U- and/or 232Th-medium (in particular, the neutron-fission progressive wave of Feoktistov and/or Teller-Ishikawa-Wood) can be such a physical consequence. The simplified model of the kinetics of accumulation and burnup in U-Pu fuel cycle of Feoktistov is developed. The results of the numerical simulation of neutron-fission wave in two-phase UO2/Fe medium on a surface of the Earth's solid core are presented. The georeactor model of 3He origin and the 3He/4He-ratio distribution in the Earth’s interior is offered. It is shown that the 3He/4He ratio distribution can be the natural quantitative criterion of georeactor thermal power. On the basis of O'Nions-Evensen-Hamilton geochemical model of mantle differentiation and the crust growth supplied by actinid shell on the boundary of liquid and solid phases of the Earth's core as a nuclear energy source (georeactor with power of 30 TW), the tentative estimation of geoantineutrino intensity and geoantineutrino spectrum on the Earth surface are given.